What causes adverse events in prehospital care? A human-factors approach. Issue 7 (16th July 2012) - Price, Roger; Bendall, Jason C; Patterson, Jillian A; Middleton, Paul M
Abstract : Background: The last decade has seen a vast amount of work directed at the investigation of patient harm events. Unfortunately, little of it has pertained to prehospital care and as such, risk remains unquantified and poorly understood in this setting. We hypothesised that adverse patient events occurring during the prehospital phase may fall into discernible patterns, and that an understanding of these patterns would be valuable in the development of mitigation strategies. Methods: A survey tool was developed with reference to the human factors literature. Paramedics in a large Australian ambulance service were asked to recall an adverse event and to nominate factors that may have contributed to its occurrence. Responses were analysed using principal components analysis in order to identify contributory factors that could be statistically grouped together in meaningful patterns. Results: The survey yielded 370 responses. Eight key single contributors and 14 groups of contributory factors were identified. Of the groups, only two were strongly associated with serious patient outcomes, such as reported significant deterioration or death. Conclusions: The deteriorating patient was identified as the leading single contributor to prehospital adverse events, and two perfect storm patient harm scenarios were found to contribute materially to adverse outcomes. This approach to identifying both single factors contributing to an incident and factors which could be grouped together in a pattern, appears useful in delineating risk in the acute prehospital setting, and warrants further exploration in this and other areas of patient safety.